Was Fiscal Policy in the Thirties a Failure? - Hansen, Alvin H. (The Review of Economics and Statistics, 1963)
tinue to neglect them for the present purpose. The specialists who now buy bills from the Treasury and then resell them to the ultimate investors are presumably being compensated for their activities. They have many alternatives. It is hard to see that they receive any economic rent that the Treasury in any way taps by its present method of auction. On the contrary, the Treasury enables those specialized abilities required to guess accurately the outcome of weekly auctions to earn a higher rent than they otherwise could. Private distribution costs are therefore higher under the present method of auction than they would be under the alternative method. Who pays these additional costs? Since we have assumed that the demand by ultimate investors is not affected, since the amount of bills is presumably not affected, since the Treasury does not succeed in imposing discriminatory prices on ultimate investors, the price paid by ultimate investors must be roughly the same whatever the method of distribution. It follows that the Treasury must pay the additional distribution costs by receiving less on the average from its bills than if it used the alternative method of auction. Two final comments. First, if this analysis is correct, it means that Brimmer's conclusion that noncompetitive bidding should be eliminated from present auctions is wrong. The introduction of such bidding reduces the unnecessary cost imposed by the Treasury on itself by the present method of bidding. Second, the defects of the present method of auction are quantitatively minor, and may be negligible, for bills because of their short maturity, large volume, and broad market. The defects are far more important for bonds and are more important, the longer the maturity. The main obstacle to using auctions to distribute longer-term securities has been the implicit assumption that the present method of auctioning bills must be used for them as well, as it has been in earlier experiments. The adoption of the alternative method would enable the Treasury to auction all securities issued, whatever their maturity, at a gain both to itself and to the economy.5